Non-bank banks : a looming menace? : how new players are changing the financial services industry - Orton, Ian (Dublin Lafferty Publications, 1994)
This book discusses activities and impact of non-bank financial institutions on global and national economies. Themes discussed include regulation and the banking environment; origin and scope of non-bank financial activities, non-bank participation in financial services markets; and financial disintermediation. Description of the activities of some companies that engage in non-bank activities (savings, credit). This include Marks & Spencer's Financial Services; Group Suez, General Electric Capital Services; Dreyfus Corporation; Sears, Roebuck among others.
lje 20/07/16
Loan
Keywords: Banks and banking -- Forecasting; Financial services industry -- Forecasting